2011
DOI: 10.1016/j.brainres.2011.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal water deprivation alters brain angiotensin system and dipsogenic changes in the offspring

Abstract: Objective Central renin–angiotensin system (RAS) plays an important role in regulating body fluid balance. The present study determined the effect of maternal dehydration on brain expression levels of angiotensinogen, angiotensin II receptor subtypes, and dipsogenic responses in offspring. Methods Pregnant rats were deprived of water during late gestation. Expressions of brain angiotensinogen, angiotensin II receptors, and dipsogenic responses were determined. Results Maternal water deprivation significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…It might be due to unpalatability of dams to water containing NaAsO 2 . Although we did not observe the obvious signs of maternal or embryonic toxicity such as maternal weight (Figure S1 ) and the number of pups (Figure S2 ) between the two groups of this study, several studies reported the possibility that maternal dehydration due to reduced water intake during pregnancy was associated with long-term physiologic effects on offspring such as development of brain function and plasma composition (Desai et al, 2005 ; Ross et al, 2005 ; Zhang et al, 2011 ). Therefore, we had to assume that behavioral inflexibility observed in mice prenatally exposed NaAsO 2 could be induced by the combinatorial effect of the toxicity of prenatal NaAsO 2 exposure and maternal dehydration.…”
Section: Discussionmentioning
confidence: 54%
“…It might be due to unpalatability of dams to water containing NaAsO 2 . Although we did not observe the obvious signs of maternal or embryonic toxicity such as maternal weight (Figure S1 ) and the number of pups (Figure S2 ) between the two groups of this study, several studies reported the possibility that maternal dehydration due to reduced water intake during pregnancy was associated with long-term physiologic effects on offspring such as development of brain function and plasma composition (Desai et al, 2005 ; Ross et al, 2005 ; Zhang et al, 2011 ). Therefore, we had to assume that behavioral inflexibility observed in mice prenatally exposed NaAsO 2 could be induced by the combinatorial effect of the toxicity of prenatal NaAsO 2 exposure and maternal dehydration.…”
Section: Discussionmentioning
confidence: 54%
“…Further studies are necessary to discriminate the precise stage responsible for the changes observed later in life. Previous studies [10][11][12][13]16,21,22,39] have shown that early challenges to osmoregulatory mechanisms involving electrolyte and/or endocrine environmental changes, lead to persistent changes in need-free and stimulated fluid intake and, while most of the work has shown perinatal osmotic alterations, they have contradictory results with regard to how they affect adult offspring fluid intake, and specifically, whether the perinatal manipulation increases or decreases water or sodium ingestion of the adult offspring. Whatever the final PM effect, sometimes the physiological result in terms of body sodium status may be similar.…”
Section: Discussionmentioning
confidence: 99%
“…angiotensin converting enzyme (ACE) inhibitors, induce an imprinting on osmoregulatory mechanisms, altering their endocrine and behavioral regulatory responses [10][11][12][13][14][15][16]. Perinatal experiences of the stimuli of sodium overload (water deprivation, dietary sodium overload) or sodium depletion (diuretics administration, repeated vomiting during the first trimester of pregnancy, etc.)…”
mentioning
confidence: 99%
“…Some of these candidates were identified during the pre-GWAS period, with others based on GWAS studies. NKX2-1 is known to interact with a number of these genes (Thome et al, 1996 ; Perrone et al, 1999 ; Stober et al, 1999 ; Marin et al, 2000 ; Naltner et al, 2000 ; Ojeda et al, 2000 ; Stoykova et al, 2000 ; Kim et al, 2002 ; Leonard et al, 2002 ; Yi et al, 2002 ; Chojnacki and Weiss, 2004 ; Cui et al, 2005 ; Ide et al, 2005 ; Reynolds and Hoidal, 2005 ; Aghajani et al, 2006 ; Sanjuan et al, 2006 ; Takahashi et al, 2006 ; Benzel et al, 2007 ; Hashimoto et al, 2007 ; Son et al, 2007 ; Takao et al, 2007 ; Kahler et al, 2008 ; Zhou et al, 2008 ; Leon et al, 2009 ; Carney et al, 2010 ; Waddington et al, 2010 ; Goulburn et al, 2011 ; Zhang et al, 2011 ; Crisafulli et al, 2012 ; Matagne et al, 2012 ; Quednow et al, 2012 ; Li T. et al, 2013 ; Trotman et al, 2013 ; Zscheppang et al, 2013 ; Luo et al, 2014 ) (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%